Heavy neutrino-antineutrino oscillations at the FCC-ee - Stefan Antusch; Jan Hajer; Bruno M. S. Oliveira (Journal of High Energy Physics, 2023)
Abstract We discuss the impact of heavy neutrino-antineutrino oscillations ( N N ¯ Os $$ N\overline{N}Os $$ ) on heavy neutral lepton (HNL) searches at proposed electron-positron colliders such as the future circular e + e − collider (FCC-ee). During the Z pole run, HNLs can be produced alongside a light neutrino or antineutrino that escapes detection and can decay into a charged lepton or antilepton together with an off-shell W boson. In this case, signals of lepton number violation (LNV) only show up in the final state distributions. We discuss how N N ¯ Os $$ N\overline{N}Os $$ , a typical feature of collider-testable low-scale seesaw models where the heavy neutrinos form pseudo-Dirac pairs, modify such final state distributions. For example, the forward-backward asymmetry (FBA) of the reconstructed heavy (anti)neutrinos develops an oscillatory dependence on the HNL lifetime. We show that these oscillations can be resolvable for long-lived HNLs. We also discuss that when the N N ¯ Os $$ N\overline{N}Os $$ are not resolvable, they can nevertheless significantly modify the theory predictions for FBAs and observables such as the ratio of the total number of HNL decays into ℓ − over ones into ℓ +, in an interval of the angle θ between the HNL and the beam axis. Our results show that N N ¯ Os $$ N\overline{N}Os $$ should be included in collider simulations of HNLs at the FCC-ee.